Power of the Fire Dragon - West, Tracey, 1965-; Howells, Graham (New York, NY Scholastic Inc, 2014)
The Dragon Masters are excited to go to Queen Rose's kingdom! But King Roland makes Drake and Rori stay behind. Then a giant four-headed dragon attacks the castle! Will Drake and Rori be able to battle the dark wizard and his powerful dragon on their own?
Appeals to 1st-3rd graders.
Reading level grade 2.
Keywords: Dragons -- Juvenile fiction; Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Wizards -- Fiction